2011
DOI: 10.1167/iovs.10-5898
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Manipulation of Primate Retinas, V: Effects of Lutein, Zeaxanthin, andn–3 Fatty Acids on Retinal Sensitivity to Blue-Light–Induced Damage

Abstract: After long-term xanthophyll deficiency, L or Z supplementation protected the fovea from blue light-induced damage, whereas adequate n-3 fatty acid levels reduced the damage in the parafovea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(115 citation statements)
references
References 58 publications
(77 reference statements)
2
112
1
Order By: Relevance
“…They play an important role as antioxidants to prevent against oxidative stress (Bernstein et al, 2016). Due to the absorbance maximum of lutein and zeaxanthin around 460 nm, both compounds act as blue filters for UV light (Barker et al, 2011). Both pigments show weak and broad emission at 550 nm max.…”
Section: Lutein and Zeaxanthinmentioning
confidence: 99%
See 1 more Smart Citation
“…They play an important role as antioxidants to prevent against oxidative stress (Bernstein et al, 2016). Due to the absorbance maximum of lutein and zeaxanthin around 460 nm, both compounds act as blue filters for UV light (Barker et al, 2011). Both pigments show weak and broad emission at 550 nm max.…”
Section: Lutein and Zeaxanthinmentioning
confidence: 99%
“…The macular pigment mainly consists of the retinal carotenoids lutein and zeaxanthin (Wustemeyer et al, 2003;Neuringer et al, 2004;Johnson et al, 2005;Leung et al, 2005;Barker et al, 2011;Lima et al, 2016). Its absorption spectrum lays between 400 and 540 nm with a peak at 460 nm.…”
Section: Fluorescence Lifetimes Of Retinal Fluorophores Ex Vivomentioning
confidence: 99%
“…2 The Age-Related Eye Disease Study (AREDS) demonstrated that daily oral supplementation with antioxidant vitamins and minerals reduced the risk of developing advanced AMD by 25% at 5 years. 4 Animal studies [5][6][7] and epidemiologic studies provide a rationale for examining the potential effects of other nutrients on the development of advanced AMD. Observational studies suggest that higher dietary intake of lutein ϩ zeaxanthin, omega-3 longchain polyunsaturated fatty acids (docosahexaenoic acid [DHA] and eicosapentaenoic acid [EPA]), or both are associated with a decreased risk of de- veloping advanced AMD.…”
mentioning
confidence: 99%
“…Lutein can act as a blue light filter absorbing between 390 and 540 nm, thereby protecting the underlying photoreceptors in the macula from photochemical damage [23]. As a powerful antioxidant, lutein may also protect the macula from oxidative stress [24][25][26].…”
Section: Does Lutein Affect Age-related Macular Degeneration (Amd)?mentioning
confidence: 99%